The Scientific Miracle of Human Creation in the Holy Quran - Hafidha Zekkour; Umaiyatus Syarifah; Eko Budi Minarno (Journal of Education and Teacher Training Innovation, 2024)
The scientific miracles in the Quran indicate God's ability to create the universe and humanity. The ayat alkawnia illustrate the stability of natural phenomena and link these Ayat to the divine cause. The stages of human creation are represented, starting from clay to the sperm, then the Elaqa, the Madagha, the bones, and finally the blowing of the spirit. Many surah, such as Al-Mu'minun and Al-Hajj, clarify these stages. These ayat reflect a scientific understanding that was not available at the time of the Quran's revelation, enhancing its status as a book of truth and affirming the connection between science and faith.